2015
DOI: 10.1159/000430236
|View full text |Cite
|
Sign up to set email alerts
|

Sox9 Activation is Essential for the Recovery of Lung Function after Acute Lung Injury

Abstract: Background/Aims: Acute lung injury (ALI) often predisposes acute respiratory distress syndrome (ARDS) in humans, and is featured with neutrophilic alveolitis, injury of the alveolar epithelium and endothelium, hyaline membrane formation, and microvascular thrombi. Although the pathogenesis of ALI is relatively well studied, the knowledge on the molecular regulation of the post-ALI lung recovery are poorly understood. Methods: Here, we used a widely applied bleomycin-induced ALI model to study the molecular mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Previous results have shown that fibroproliferation is a stereotypical part of the normal repair process in ALI/ARDS, which is characterized by intra-alveolar accumulation of fibroblasts and collagen deposition [21-24]. Other reports have shown that excessive fibroproliferation is associated with poorer outcomes [23, 25]. Fibrocytes participate in bleomycin models of pulmonary fibrosis [26].…”
Section: Introductionmentioning
confidence: 99%
“…Previous results have shown that fibroproliferation is a stereotypical part of the normal repair process in ALI/ARDS, which is characterized by intra-alveolar accumulation of fibroblasts and collagen deposition [21-24]. Other reports have shown that excessive fibroproliferation is associated with poorer outcomes [23, 25]. Fibrocytes participate in bleomycin models of pulmonary fibrosis [26].…”
Section: Introductionmentioning
confidence: 99%
“…Lung fibrosis is induced in certain cancer patients treated with BLEOMYCIN with molecular mechanisms largely unknown. Bleomycin is the mostly used chemical in inducing lung fibrosis in animal models [8, 51]. Both FGF-2 and TGF-β signaling pathways play major roles in the fibrosis process and GAGs are co-regulators of both FGF-2 and TGF-β pathways [54, 55].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, Bleomycin also induces lung inflammation that lead to fibrosis and rapid death in certain cancer patients. The unexplainable side effect of bleomycin makes it an effective reagent in inducing lung fibrosis in a variety of animal models [6-8]. Up to date, it is still unknown the molecular targets of bleomycin that causes lung fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Sox9 turned out to be a direct miR-101 target, and its suppression adequate recovery after lung injury. Therefore, appropriate epithelial Sox9 expression appears to be essential for proper lung recovery after lung injury [68]. One of the first miRNAs with a role in preventing fibrosis was identified by Pandit et al [69] .…”
Section: Mirnas In Mucosal Immune Functionsmentioning
confidence: 99%
“…For example miR-21 and miR-122a directly influence mucosal permeability by regulating the expression of epithelial tight junctions [62, 63]. In later stages of mucosal inflammation including the resolution, remodeling and repair processes miRNAs are also critically involved and e.g., promote adequate recovery such as miR-101 which is important for proper lung recovery after lung injury [68]. Epithelial let-7d is essential in preventing remodeling and development of pulmonary fibrosis after inflammation and lung injury [69].…”
Section: Figmentioning
confidence: 99%